Implementasi Customer Relationship Management (CRM) Berbasis Web dalam Meningkatkan Penjualan pada Perusahaan Almazone - Setyawan, Moh Dodi; Supriyono, Supriyono; Fithri, Diana Laily; Adiyono, Soni; Romadhon, Zainur; Widodo, Anteng; Setiaji, Pratomo (Jurnal SITECH : Sistem Informasi dan Teknologi, 2024)
Almazone is a company that operates in the online clothing sales sector. The online media used to sell its products include Facebook. The company develops Facebook Ads that are creative and attract interest, providing opportunities for potential buyers to explore their clothing collections. Almazone is currently facing several obstacles, including: Data collection has not been properly computerized, so that data recording is ineffective and inefficient, and also opens up big opportunities for errors and data loss. The company does not know whether the product being sold is good or not because there is no specific module used to analyze the assessment of products purchased by customers. Customer loyalty is disappearing because there is no system that can provide criticism and suggestions and is also unable to manage and analyze customers. One approach that can help with the obstacles described above is to implement website-based customer relationship management (CRM) and CSAT.